2016
DOI: 10.1021/acscatal.6b00200
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Working and Counter Electrode Surface Area Ratios on the Dissolution of Platinum under Electrochemical Conditions

Abstract: The potential variation of Pt counter electrode (CE) in a three-electrode configuration is monitored as the potential of Pt working electrode (E WE ) follows a triangleshaped program in 0.5 M aqueous H 2 SO 4 . The spontaneously adopted CE potential (E CE ) is reported for different values of the ratio of geometric surface areas of WE and CE (A geom,WE /A geom,CE ). The E CE versus time (t) transients are non-linear and resemble charging/discharging curves. In the case of A geom,WE > A geom,CE , E CE adopts hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 50 publications
1
65
0
Order By: Relevance
“…We claim herein that platinum oxide species formed on the Pt anode may be dissolved in the H 2 SO 4 and cationic Pt oxide species can be electrodeposited on the Ni42 steel (Figure f). This assumption seems to be founded for example, Mitsushima et al . investigated the dissolution of Pt in the presence of O 2 in sulfuric acid and postulated the following dissolution reaction: truePtO2+normalH++4ptnormalH2normalO4pt4ptPt(OH)3+ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We claim herein that platinum oxide species formed on the Pt anode may be dissolved in the H 2 SO 4 and cationic Pt oxide species can be electrodeposited on the Ni42 steel (Figure f). This assumption seems to be founded for example, Mitsushima et al . investigated the dissolution of Pt in the presence of O 2 in sulfuric acid and postulated the following dissolution reaction: truePtO2+normalH++4ptnormalH2normalO4pt4ptPt(OH)3+ …”
Section: Resultsmentioning
confidence: 99%
“…This assumption seems to be found- [45] and 72.2 eV (Pt(OH) 2 ), [45] and two 4f 5/2 peaks located at 74.6 eV (Pt 0 ) and 75.6 eV (Pt(OH) 2 ) binding energy, respectively (f). ed [53][54][55] for example, Mitsushima et al [53] investigated the dissolution of Pt in the presence of O 2 in sulfuric acid and postulated the following dissolution reaction:…”
Section: Samplementioning
confidence: 89%
“…For revealing this complete Pt dissolution mechanism, enormous research efforts have been made to evaluate the characteristics of these surface oxides (i.e. PtO x , x = 1 or 2), the valence of the dissolved constituents, the influence of potential change, temperature, pH, and the mass-transport on the reactions participated [2][3][4]. Evidently, Pt is not as stable as it is anticipated.…”
mentioning
confidence: 99%
“…However, further experimental results demonstrated that not only in the acidic, but also in the alkaline media, both electrochemical and chemical dissolution of Pt would lead to the deposition of Pt on the working electrode if there is not any ion exchange membrane employed in the electrochemical setup. In consideration of these results obtained, they finally gave several valuable suggestions: (1) purifying the electrolyte before HER process, (2) replacing the Pt with other stable counter electrodes, (3) applying the ion exchange membrane to the setup preventing the Pt transfer across the working and counter electrodes.…”
mentioning
confidence: 99%
“…We claim herein that platinum oxide species formed on the Pt anode may be dissolved in the H 2 SO 4 and cationic Pt oxide species can be electrodeposited on the Ni42 steel (Figure f). This assumption seems to be founded for example, Mitsushima et al . investigated the dissolution of Pt in the presence of O 2 in sulfuric acid and postulated the following dissolution reaction: truePtO2+normalH++4ptnormalH2normalO4pt4ptPt(OH)3+ …”
Section: Resultsmentioning
confidence: 87%